MASS MEDIA AND IMAGE OF POLITICAL ACTORS - Agesti Maulandari; Senja Yustitia; Muhammad Edy Susilo (The Indonesian Journal of Communication Studies, 2017)
Things or events about politics are always attracted the attention of mass media to be news materials. The news about political actors in the mass media will form the self-image of the political actors in the eyes of the public Current media conditions are widely used as a political vehicle, made the news presented by the media is difficult to objective even the media prioritize the interests of this media. It can affect the image of someone who became the object of news. The formulation of the problem in this research is how the reception of the audience towards the image of Basuki Tjahaja Purnama through the news in mass media and what the factors that can affect the audience in the reception to the image of Basuki Tjahaja Purnama through the mass media. The purpose of this study is to determine how the reception of audience to image Basuki Tjahaja Purnama through mass media and also what factors affect the audence during the reception. Researchers used Stuart Hall’s reception analysis theory to know how reception of audience to the image Basuki Tjahaja Purnama in mass media. The results obtained are the researchers found two sources who are in the position of the dominant-hegemonic and and four others are in the position of the negotiated reading. Researchers did not find the audience included in the category of the oppositional reading. The conclusion of this study is that not always the theory of reception analysis proposed by Stuart Hall can produce three audiences positions. Its because, audience is dynamic, not static. Then, factors that influence the reception of audiences are four, media usage that includes the frequency of news consuming and media selection, religion, culture and fanaticism.